The Effect of QR, ITO and TATO On NPM Tobacco Companies - Alya Nurhaliza; Indar Khaerunnisa (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2025)
The study aims to determine and prove the effect of Quick Ratio, Inventory Turnover and Total Asset Turnover on Net Profit Margin tobacco subsector companies on Indonesia Stock Exchange period 2015-2024. The research method used is quantitative. Data analysis using multiple linear regression techniques using 20 spss application. The results of the test t Quick Ratio test obtained sig. 0.552 > 0.05 and tcount < ttable 0.603 < 2.056 means Ho1 is accepted and Ha1 is rejected, Inventory turnover obtained sig 0.062 > 0.05 and tcount < ttable -1,950 < 2.056 means Ho2 is rejected Ha2 is rejected, Total Asset Turnover obtained sig 0.002 < 0.05 and tcount > ttable 3.374 > 2.056 means Ho3 is rejected and Ha3 is accepted. the results of the F test obtained sig. 0.000 < 0.05 and tcount > ttabel 8,506 > 2,975 which means that Ho4 is rejected and Ha4 is accepted. It can be concluded that partially Quick Ratio and Inventory Turnover have no significant effect on Net Profit margin while Total Asset Turnover variable has significant effect on Net Profit Margin. Simultaneously Quick Ratio, Inventory Turnover and Total Asset Turnover have a significant effect on Net Profit Margin.